Pelaksanaan Putusan Kasasi Mahkamah Agung secara Sukarela oleh Badan Usaha Milik Negara: Studi Kasus Ganti Rugi Nasabah oleh Bank BRI - M. Rasya Anugrah Putra Rafa; Aldan Nugraha; Hagi Atful Ginani; Muhammad Hasbi Azwari Rahmat; Hilmanul hamdi Muhammad (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze the voluntary implementation of a Supreme Court cassation decision by a State-Owned Enterprise (SOE) through a case study of customer compensation carried out by Bank Rakyat Indonesia (BRI). The analysis focuses on the binding legal force of cassation decisions that are final and enforceable (inkracht van gewijsde), the legal compliance of SOEs as subjects of private law, and the legal implications for legal certainty and the protection of customers’ rights as financial service consumers. This research employs a normative legal research method using statutory, conceptual, and case approaches, analyzed qualitatively based on primary, secondary, and tertiary legal materials. The results indicate that Supreme Court cassation decisions possess binding legal force and must be executed by all parties without exception, including SOEs. The voluntary execution of the cassation decision by Bank BRI in the customer compensation case reflects legal compliance and good faith, while affirming that SOEs do not enjoy legal immunity in civil disputes. Furthermore, such voluntary implementation has positive implications for strengthening legal certainty, protecting customers’ rights, enhancing the institutional image and corporate governance of SOEs, and improving the effectiveness of civil law enforcement in Indonesia. Therefore, the voluntary execution of court decisions by SOEs can serve as an ideal model for achieving substantive justice and increasing public trust in the judicial system.